EFFECTIVENESS OF BACK MASSAGE USING VCO WITH LEVEL AROMATHERAPY ON SLEEP QUALITY IN THE ELDERLY - Nurul Faidah (Jurnal Ilmu Keperawatan Jiwa, 2024)
The elderly experience a decrease in the effectiveness of sleeping at night by 70% to 80% compared to young people. Back massage with VCO and Lemongrass Aromatherapy, one of the complementary therapies, can also be used to treat sleep problems. The purpose of this study was to determine the effectiveness of back massage with VCO and lemongrass aromatherapy on the sleep quality of the elderly. The design of this study was pre-experimental using a group pretest-posttest design. This research will be carried out in the working area of ​​North Denpasar III. The study was conducted in March 2021. The sample in this study was 34 respondents. The sampling technique used in this study is non-probability sampling, namely purposive sampling. The data collection instrument used in this study was a measuring instrument for sleep quality. For the implementation of back massage with VCO and the implementation of lemongrass aromatherapy and standard operating procedures (SOP). Research gets permission or ethical clerence. The research was carried out 6 times. The results of the study in the group given back massage intervention with VCO were 11 (64.7%) poor sleep quality, in the group given lemongrass aromatherapy 12 (70.6%) poor sleep quality. The results of the analysis in both groups were for the group that was given back massage with VCO, the P value was 0.003 while in the group that was given the lemongrass aromatherapy intervention, the p value was 0.001. Based on the results of the effectiveness analysis in both groups, 0.17 results were obtained, which means that both interventions have an effect on the sleep quality of the elderly.